The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.33448/rsd-v11i2.25772
|View full text |Cite
|
Sign up to set email alerts
|

Comparação dos perfis bioquímicos e hematológicos de pacientes com COVID-19 em seus diferentes desfechos: alta hospitalar e óbito

Abstract: Introdução: O vírus causador da COVID-19, SARS-CoV-2, apresenta como principal foco de comprometimento o trato respiratório, ainda hoje com muitos pacientes evoluindo para a forma mais grave. Por isso, deve-se identificar precocemente sinais e sintomas da COVID-19, além de possíveis fatores de risco e sinais de mau prognóstico envolvidos na progressão da doença. Objetivo: Desta forma, o presente trabalho teve por objetivo avaliar exames bioquímicos, hematológicos e de coagulação em pacientes diagnosticados com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
2
0
2
Order By: Relevance
“…Regarding health-related physical fitness tests, significant improvements were observed in the 30-s chair-stand test for the severe and moderate COVID-19 groups and control group after 8 weeks of intervention, independent of changes in anthropometric and body composition differences, corroborating the findings of Li et al ( Li et al, 2021 ) and Dalbosco-Salas et al ( Dalbosco-Salas et al, 2021 ) after 6 and 9 weeks of tele-exercises, respectively, posthospital discharge for COVID-19. The lack of significant differences in anthropometric and body composition was explained by a lockdown, in which people could not move freely and, consequently, spent low energy ( Silva et al, 2022 ). It is worth mentioning that the participants needed sufficient intra- and inter-coordination to perform the exercises correctly and overcome inflammation (measured via CRP).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding health-related physical fitness tests, significant improvements were observed in the 30-s chair-stand test for the severe and moderate COVID-19 groups and control group after 8 weeks of intervention, independent of changes in anthropometric and body composition differences, corroborating the findings of Li et al ( Li et al, 2021 ) and Dalbosco-Salas et al ( Dalbosco-Salas et al, 2021 ) after 6 and 9 weeks of tele-exercises, respectively, posthospital discharge for COVID-19. The lack of significant differences in anthropometric and body composition was explained by a lockdown, in which people could not move freely and, consequently, spent low energy ( Silva et al, 2022 ). It is worth mentioning that the participants needed sufficient intra- and inter-coordination to perform the exercises correctly and overcome inflammation (measured via CRP).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, machine learning has been an important tool to help doctors diagnose various diseases [33,34], including COVID-19 [35][36][37]. Studies have made use of this technology to detect COVID-19, either through images such as x-rays or CT scans, or through laboratory tests [38][39][40], since many clinical studies have shown hematological changes in infected patients [41][42][43][44]. While others focus on analyzing how these parameters vary throughout the course of the disease and their relationship with more serious clinical outcomes [45][46][47].…”
Section: Of 29mentioning
confidence: 99%
“…Ratificando os dados apresentados, Silva et al (2022) comparou os perfis bioquímicos e hematológicos de pacientes com COVID-19 e encontrou valores de glicose elevados nos pacientes que tiveram alta hospitalar, mas mais ainda superiores no grupo que foi ao óbito. Analogamente, Chen et al (2021) destacou a necessidade do monitoramento glicêmico em pacientes acometidos por SARS-CoV-2, tendo em vista que a associação do vírus com a hiperglicemia aumenta as chances de piora clínica.…”
Section: Análise Estatística Realizada Por Meio Do Teste T De Student...unclassified
“…No contexto do aumento das taxas leucocitárias, ambos os grupos que tiveram o desfecho clínico para o óbito (masculino e feminino) apresentaram valores mais elevados em relação aos grupos que tiveram desfecho clínico para alta hospitalar. Além disso, ao comparar os parâmetros laboratoriais do momento da admissão ao desfecho clínico, os grupos que foram ao óbito demonstraram, com o decurso do tempo, o aumento dos valores dos parâmetros, condição não evidenciada nos grupos que evoluíram para alta hospitalar.Foi possível corroborar os dados de hemoglobina e leucócitos com o estudode Silva et al (2022), no qual, ao realizarse a comparação dos perfis bioquímicos e hematológicos de pacientes com COVID-19 em seus diferentes desfechos (alta hospitalar e óbito), notou-se a hemoglobina reduzida e os leucócitos aumentados na amostra que evoluiu para o óbito. Vale ressaltar, ainda, a conclusão desse estudo, a qual discorreu que as variações encontradas nos parâmetros bioquímicos e hematológicos são constantes em pacientes com coronavírus, sobretudo nos que evoluíram para o óbito.…”
unclassified